Краєзнавчий навчальний курс "Моя Черкащина" в закладах загальної середньої освіти - Чепурна, Н.; Мельниченко, В. (Краєзнавство, 2024)
У статті наголошується на актуальності викладання у закладах загальної середньої освіти історії рідного краю як важливого чинника формування в сучасної учнівської молоді національно-історичної свідомості і патріотичних якостей. З метою реалізації цього суспільно значимого завдання для шкіл Черкаської області розроблено і схвалено Міністерством освіти і науки програму та навчально-методичне забезпечення викладання в 7–11 класах курсу «Моя Черкащина» (історія краю від найдавніших часів до сучасності). Розкривається зміст історико-краєзнавчого курсу і досвід його впровадження в освітній процес. The article emphasizes the relevance of teaching the history of the native land in institutions of general secondary education as an important factor in the formation of national-historical consciousness and patriotic qualities in modern schoolchildren. In order to implement this socially significant task in the schools of the Cherkasy region, the program and educational and methodological support for teaching the course «My Cherkasy» (history of the region from ancient times to the present) was developed and approved by the Ministry of Education and Science in grades 7–11. The content of the historical and local history course and the experience of its implementation in the educational process are revealed.